A Metamaterial Loaded High Gain Low Profile RHCP Microstrip Antenna for X-Band Applications - Manoj Kumar Shrivastava; Ripudaman Singh; Diptiranjan Samantaray; Azharuddin Khan; Anil Kumar Gautam; Amit Kumar Singh (IEEE Access)
This paper presents the design of a right-hand circularly polarized (RHCP) microstrip antenna loaded with metamaterial to achieve high-gain performance. The metamaterial (MTM), a $5 × 5~$ array of unit cells with a negative refractive index, is designed on one-sided FR4 dielectric material with dimensions $0.79λ _{0} × 0.79λ _{0} × 0.023λ _{0}$ , where $λ _{0}$ is the free-space wavelength at 8.76 GHz. Both the antenna and the unit cells are designed on an FR4 substrate with a loss tangent of 0.02 and relative permittivity of 4.4. The antenna and MTM maintain the same area, with an air gap of 1 mm between them. The overall structure achieves a gain of 8.1 dBic at 9.5 GHz with stacking, compared to 4.4 dBic without the MTM stacking. The measured bandwidth of the proposed antenna is 1.98 GHz (8.76-10.74 GHz), which falls within the lower X-band, making it suitable for both military and maritime radar applications.